MODERATISME HUKUM SEBAGAI FONDASI MASYARAKAT ISLAM - Zaenal Mutaqin; Ridzwan Ahmad (TEMALI : Jurnal Pembangunan Sosial, 2019)
This study is a discussion on the concept of moderate (wasatiyyah) in Islamic law from the perspective of Yusuf al-Qaradawi. It aims to provide an understanding of the concept of wasatiyyah in the face of two extreme streams: modernism and liberalism. The concept of wasatiyyah is characterized by ijtihad based on maqasid (the goals of Law), integration between shari'a, simple view, performing fiqh al-waqi ', dialogue (hiwar) and tolerance. While the basis of its application is based on ijtihad maqasidi, understanding the text within the framework of the current situation, distinguishing between eternal maqasid and changing wasilah, adjusting the qat'i and zhanni, distinguishing the meaning between mu'amalah (custom) and excess in worship (ifrat) and neglect (tafrit). The correct understanding and implementation of the comprehensive wasatiyyah concept will prove that Islam is a religion that brings tranquility and happiness to all human beings on earth based on rahmatan li al-'alamin. This study found that Yusuf al-Qaradawi wasatiyyah thought was based on the goal of Islamic Law (maqasid al-syari’ah). It is precisely the practice of wasatiyyah to be in line with the maqasid al-syari’ah in the framework of making Islamic shari'ah a solution to the problems of the umma.